The future of financing for HIV services in Uganda and the wider sub-Saharan Africa region: should we ask patients to contribute to the cost of their care? - Tom Kakaire; Walter Schlech; Alex Coutinho; Richard Brough; Rosalind Parkes-Ratanshi (BMC, 2016)
Abstract Whilst multi-lateral funding for HIV/AIDS dramatically increased from 2004 to 2008, it has largely plateaued in the last 8 years. Across sub-Saharan Africa, up to 20 % of total spending on health is used for HIV services, and of this over 85 % is estimated to come from international funding rather than in-country sources. In Uganda, the fiscal liability to maintain services for all those who are currently receiving it is estimated to be as much as 3 % of Gross Domestic Product (GDP). In order to meet the growing need of increased patient numbers and further ART coverage the projected costs of comprehensive HIV care and treatment services will increase substantially. Current access to HIV care includes free at point of delivery (provided by Ministry of Health clinics), as well as out-of-pocket financing and health insurance provided care at private for- and not for- profit facilities. The HIV response is funded through Ugandan Ministry of Health national budget allocations, as well as multilateral donations such as the President's Emergency Plan for AIDS in Africa (PEPFAR) and Global Fund (GF) and other international funders. We are concerned that current funding mechanism for HIV programs in Uganda may be difficult to sustain and as service providers we are keen to explore ways in which provide lifelong HIV care to as many people living with HIV (PLHIV) as possible. Until such time as the Ugandan economy can support universal, state-supported, comprehensive healthcare, bridging alternatives must be considered. We suggest that offering patients with the sufficient means to assume some of the financial burden for their care in return for more convenient services could be one component of increasing coverage and sustaining services for those living with HIV.